2017
DOI: 10.1002/mc.22739
|View full text |Cite
|
Sign up to set email alerts
|

Serum HOTAIR and GAS5 levels as predictors of survival in patients with glioblastoma

Abstract: Circulating long non-coding RNAs (lncRNAs) are a new class of cancer biomarkers.However, their significance in predicting outcomes in glioblastoma patients is unclear.We measured the levels of six known oncogenic lncRNAs-CRNDE, GAS5, H19, HOTAIR, MALAT1, and TUG1 in serum samples from 106 patients with primary glioblastoma and analyzed their association with outcomes. High levels of HOTAIR were associated with decreased probability of 2-year overall survival (adjusted hazard ratio [HR] = 2.04; 95% confidence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 45 publications
(59 reference statements)
5
73
0
1
Order By: Relevance
“…Emerging evidence identifies GAS5 as a potential prognostic and diagnostic marker in hepatocellular carcinoma. 21 In this study, depression of GAS5 reduced the sensitivity of U87 cells that had high GAS5 levels to cisplatin by inhibiting cell viability, colony formation, and promoting cell apoptosis. 19 For research in glioma, GAS5 exerts an inhibitory effect on cell proliferation and malignancy of human glioma stem cell.…”
Section: Gas5 Mutes Cisplatin-activated Autophagy In a Mtor-dependementioning
confidence: 63%
“…Emerging evidence identifies GAS5 as a potential prognostic and diagnostic marker in hepatocellular carcinoma. 21 In this study, depression of GAS5 reduced the sensitivity of U87 cells that had high GAS5 levels to cisplatin by inhibiting cell viability, colony formation, and promoting cell apoptosis. 19 For research in glioma, GAS5 exerts an inhibitory effect on cell proliferation and malignancy of human glioma stem cell.…”
Section: Gas5 Mutes Cisplatin-activated Autophagy In a Mtor-dependementioning
confidence: 63%
“…were associated with increased probability of OS and DFS rates in patients with GBM. 102 These results suggested that GAS5 might have great potential to be used as a therapeutic target and biomarkers for GBM. Head and neck cancer (HNC) is a heterogeneous group of cancers originating from the upper aero-digestive tract and one of the ten most frequent cancers worldwide.…”
Section: Clinical Relevancementioning
confidence: 91%
“…Higher HOTAIR levels were detected in patients' total serum and in exosomes when compared with healthy controls. 108 Shen et al 109 also reported that high levels of HOTAIR and low levels of GAS5 in serum associated with a reduced probability of 2-year survival, suggesting its potential as prognostic biomarkers.…”
Section: Circulating Tumour Nucleic Acidsmentioning
confidence: 98%